Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1680/jgeot.17.p.203
|View full text |Cite
|
Sign up to set email alerts
|

Empirical approach based on centrifuge testing for cyclic deformations of laterally loaded piles in sand

Abstract: A systematic study into the response of monopiles to lateral cyclic loading in medium dense and dense sand was performed in beam and drum centrifuge tests. The centrifuge tests were carried out at different cyclic load and magnitude ratios, while the cyclic load sequence was also varied. The instrumentation on the piles provides fresh insights into the ongoing development of net stresses, bending moments and deflections as cycling progresses. Parallels between the test results and corresponding cyclic triaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 30 publications
(31 reference statements)
5
33
3
Order By: Relevance
“…The power-law coefficient A has been found to vary with ζ b and ζ c (Leblanc et al 2010;Nicolai and Ibsen 2014), and the power-law exponent α has often been reported as a constant within individual studies (Leblanc et al 2010;Nicolai and Ibsen 2014;Albiker et al 2017). However, Truong et al (2019) suggested that α varies with ζ c and D R . This paper investigates only a single value of ζ c and D R .…”
Section: Ratcheting Responsementioning
confidence: 99%
See 2 more Smart Citations
“…The power-law coefficient A has been found to vary with ζ b and ζ c (Leblanc et al 2010;Nicolai and Ibsen 2014), and the power-law exponent α has often been reported as a constant within individual studies (Leblanc et al 2010;Nicolai and Ibsen 2014;Albiker et al 2017). However, Truong et al (2019) suggested that α varies with ζ c and D R . This paper investigates only a single value of ζ c and D R .…”
Section: Ratcheting Responsementioning
confidence: 99%
“…The response of these large-diameter hollow steel piles has been the subject of much recent research because their geometry and load regime differ from piles traditionally used for offshore oil and gas and onshore applications. Monopiles are subjected to long-term multidirectional cyclic lateral loading caused by a combination of wind, waves, and current loads, which has been shown in model tests to cause accumulated displacement or rotation of the foundation (e.g., Li et al 2010;Truong et al 2019) and evolution of foundation stiffness (Leblanc et al 2010) and energy dissipation (Abadie et al 2019). Accumulated rotation of the foundation is of particular concern because turbine manufacturers specify strict rotation limits, and changes to foundation stiffness and energy dissipation impact the dynamic response of the foundation and can enhance dynamic amplification of loads and increase fatigue damage of the OWT structure (Bhattacharya 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LeBlanc et al, 2010;Abadie et al, 2018) and iii) reduced-scale centrifuge tests (e.g. Georgiadis et al, 1992;Verdure et al, 2003;Rosquoet et al, 2007;Li et al, 2010;Hededal, 2013, 2014;Klinkvort et al, , 2019Choo and Kim, 2015;Truong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the model testing setup is usually solely either one-way or two-way, whereas the loading on an offshore wind foundation is a combination of the two with cyclic load packets of different means and ranges. However, recent scaled tests by Richards et al [17], Truong et al [18], and Abiker and Achmus [19] show that the effect of two-way loading is less severe than the ones previously reported in LeBlanc et al [11]. It is shown that the load factor for partial two-way loading factor T c can be reduced from 4, as originally presented, to a number in the range of 2-3, which has a significant impact on the effect of accumulated rotation considering the total number of cycles in a given storm.…”
Section: Additional References In Sandmentioning
confidence: 99%